Familial Monkeypox Virus Infection Involving 2 Young Children - Pascal Del Giudice; Agnes Fribourg; Laurent Roudiere; Juliette Gillon; Anne Decoppet; Mathieu Reverte (Emerging Infectious Diseases, 2023)
We report intrafamilial transmission of monkeypox virus to all members of a family (father, mother, and 2 children). Case reports in young children have been extremely rare during the 2022 mpox outbreak. Their clinical signs were mild, and clinical diagnosis would be difficult without knowledge of the father’s monkeypox virus infection.